Temperature dependence of the optical properties of silicon nanocrystals - Zacharias, Marios; Kelires, Pantelis C. (My University, 2020)
© 2020 American Physical Society. Silicon nanocrystals (SiNCs) have been under active investigation in the last decades and have been considered as a promising candidate for many optoelectronic applications including highly efficient solar cells. Some of the fundamental properties of interest in these nanostructures is the temperature dependence of their optical absorption onset and how this is controlled by different passivation regimes. In the present work we employ first-principles calculations in conjunction with the special displacement method to study the temperature dependence of the band gap renormalization of freestanding hydrogen-terminated, and oxidized SiNCs, as well as matrix-embedded SiNCs in amorphous silica, and we obtain good agreement with experimental photoluminescence data. We also provide strong evidence that the electron-phonon interplay at the surface of the nanocrystal is suppressed by oxidation and the surrounding amorphous matrix. For the matrix-embedded SiNCs, we show a high correlation between the temperature dependence of the band gap and the Si-Si strained bonds. This result emphasizes the immanent relationship of electron-phonon coupling and thermal structural distortions. We also demonstrate that, apart from quantum confinement, Si-Si strained bonds are the major cause of zero-phonon quasidirect transitions in matrix-embedded SiNCs. As a final point, we clarify that, unlike optical absorption in bulk Si, phonon-assisted electronic transitions play a secondary role in SiNCs.
Keywords: Silicon nanocrystals (SiNCs)